TEACHER’S STRATEGIES IN GETTING STUDENTS’ ATTENTIONS DURING TRANSITION (A CASE STUDY ON AN ENGLISH TEACHER IN AN ELEMENTARY SCHOOL IN BANDUNG - Wulan Fauzia (Journal of English and Education, 2013)
This article focuses on the teacher’s strategies in getting the students’ attention during transition. Since students could not proceed classroom activities without paying attention to the teacher’s instruction, various strategies in getting the students’ attention are necessary. This study employed a qualitative research method, particularly a case study design. The data were collected through five observations and two interviews. The participants of this study were an English teacher and a class of third grade students in a state elementary school in Bandung. The findings revealed that the teacher used desisting, chant, sound, clapping and singing a song in getting students’ attention. Keywords:Transitional strategies, classroom management